Effect of long-term exposure to fine particulate matter on lung function decline and risk of chronic obstructive pulmonary disease in Taiwan: a longitudinal, cohort study. Issue 3 (March 2018) - Guo, Cui; Zhang, Zilong; Lau, Alexis K H; Lin, Chang Qing; Chuang, Yuan Chieh; Chan, Jimmy; Jiang, Wun Kai; Tam, Tony; Yeoh, Eng-Kiong; Chan, Ta-Chien; Chang, Ly-Yun; Lao, Xiang Qian
Summary: Background: Information on the effects of long-term exposure to fine particulate matter with an aerodynamic diameter of 2·5 μm or less (PM2·5 ) on lung health is scarce. We aimed to investigate the associations between long-term exposure to PM2·5, lung function, and chronic obstructive pulmonary disease (COPD) in a large-scale longitudinal cohort. Methods: We included 285 046 participants aged 20 years or older from the Taiwan MJ Health Management Institution cohort, who were recruited between 2001 and 2014 and had spirometric tests during the medical examination visit. We used a satellite-based spatiotemporal model to estimate the 2-year average ground concentration of PM2·5 (for the calendar year of each participant's medical examination and for the previous year) at each participant's address. We used the generalised linear mixed model to examine the associations between PM2·5 concentrations and lung function and the Cox proportional hazard regression model with time-dependent covariates to investigate the PM2·5 effects on COPD development. Findings: Every 5 μg/m 3 increment in PM2·5 was associated with a decrease of 1·18% for forced vital capacity (FVC), 1·46% for forced expiratory volume in 1 s (FEV1 ), 1·65% for maximum mid-expiratory flow (MMEF), and 0·21% for FEV1 :FVC ratio. The decrease accelerated over time. Additional annual declines were observed for FVC (0·14%), FEV1 (0·24%), MMEF (0·44%), and FEV1 :FVC ratio (0·09%). Compared with the participants exposed to the first quartile of PM2·5, participants exposed to the fourth, third, and second quartiles of PM2·5 had a hazard ratio of 1·23 (95% CI 1·09–1·39), 1·30 (1·16–1·46), and 1·39 (1·24–1·56) for COPD development, respectively. Interpretation: Long-term exposure to ambient PM2·5 is associated with reduced, and faster declines in, lung function. Long-term exposure to ambient PM2·5 is also associated with an increased risk of the incidence of COPD. This study reinforces the urgency of global strategies to mitigate air pollution for improvement of pulmonary health and prevention of COPD. Funding: Environmental Health Research Fund of the Chinese University of Hong Kong and PhD Studentship of the Chinese University of Hong Kong.